Soft-skills training, locus of control, and labor market outcomes of youth: Evidence from a randomized intervention in Kenya - Abay, Kibrom A.; Alzua, Maria Laura; Barasa, Laura; Machio, Phyllis Mumia; Tabe-Ojong, Martin Paul Jr. (International Food Policy Research Institute, 2024)
Africa has the youngest population in the world, but African economies are not creating enough high-productivity jobs, and rates of youth unemployment thus remain a major challenge in the region. Several supply- and demand-side factors may explain these trends, including skill gaps. While traditional technical and vocational education and training (TVET) centers address important gaps in hard (technical) skills, soft-skills trainings have not yet received sufficient attention in the African context. We evaluate the overall and heterogenous impact of a gender-sensitive soft-skills training that aimed to address youths’ unique interests, preferences, and labor market constraints in Kenya. We also examine whether the presence (or absence) of complementary noncognitive skills, such as locus-of-control skills, moderates the impact of the soft-skills training. We use a randomized controlled trial to evaluate the effectiveness of a soft-skills training to support young men and women in making the transition from school to work in Kenya. Our evaluation combines baseline, midline, and endline data to understand the dynamics of labor market transitions for youth. We find that although the soft-skills training prepared youth for the labor market by improving their willingness, expectations, and preparedness for jobs, the impact of the soft-skills training on ultimate labor market outcomes varies across individuals with varying psychological traits. The training improved labor market outcomes for those with internal locus of control but not for individuals who lack these attributes. One standard deviation increase in (internal) locus of control is associated with a 5 percentage-point increase in the impact of the soft-skills training on probability of participation in income-earning activities. We also find that returns to locus of control and the soft-skills training are higher for females than males.